Macroautophagy in Endogenous Processing of Self- and Pathogen-Derived Antigens for MHC Class II Presentation - Duraes, Fernanda V.; Niven, Jennifer; Dubrot, Juan; Hugues, Stéphanie; Gannagé, Monique (Frontiers in Immunology, 2015)
Although autophagy is a process that has been studied for several years its link with antigen presentation and T cell immunity has only recently emerged. Autophagy, which means “self-eating”, is important to maintain cell homeostasis and refers to a collection of mechanisms that delivers intracellular material for degradation into lysosomes. Among them, macroautophagy pathway has many implications in different biological processes, including innate and adaptive immunity. In particular, macroautophagy can provide a substantial source of intracellular antigens for loading onto MHC class II molecules, using the alternative MHC class II pathway. Through autophagosomes, endogenous self-antigens, as well as antigens derived from intracellular pathogens can be delivered to MHC class II compartment and presented to CD4+ T cells. The pathway will therefore impact both peripheral T cell tolerance and the pathogen specific immune response. This review will describe the contribution of autophagy to intracellular presentation of endogenous self- or pathogen derived-antigens via MHC class II and its consequences on CD4+ T cell responses.